International capital transfers with public guarantees: A principal-agent analysis - Volker Stüven (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
The financial needs of corporations are generally met by borrowing in financial markets and equity participation of investors. In a similar way countries are able to obtain necessary external financing through international loans or by attracting foreign direct investment. In the case of developing countries foreign aid constitutes an additional source of foreign capital inflows. Looking at the major borrowers in Latin-America with severe debt service problems it can be stated that foreign borrowing clearly dominates the external financial structure of these countries, with foreign aid flows being negligible. The heavy reliance on foreign debt in these countries has triggered proposals that recommend a stronger role of FDI as a mean for solving the debt problems .
Keywords: 330; Internationaler Transfer; Kapitalmobilität; Prinzipal-Agent-Theorie; Theorie; Entwicklungsländer